The Influence of Mg2+ Ions on the In Vitro Efficacy of Chitosan-Titanium Dioxide Nanotubes (CTNTs) Scaffolds - Siew Shee Lim; Shui Wei Kho; Nehemiah Li Heng Ang; Cheng Heng Pang; Hwei-San Loh (Advances in Polymer Technology)
Low mechanical strength and lack of osteoconductive cues are problems associated with chitosan-based scaffolds. This research aimed to fabricate reinforced chitosan-titanium dioxide (TiO2) nanotubes (CTNTs) scaffolds attributed to the enhanced biocompatibility and physical properties of TiO2 nanotubes (TNTs). The incorporation of hydrothermally synthesized TNTs at weight percent of 16 into chitosan was achieved via direct blending and lyophilization. CTNTs scaffolds were further subjected to 24-h adsorption in MgCl2 solutions of 0.5 mM, 1 mM, 2.5 mM, and 5 mM at physiological pH. The adsorption affinity of CTNTs towards Mg2+ ions was high and mainly attributed to the macroporosity of scaffolds and nanocavities of TNTs. The maximum monolayer adsorption capacity of CTNTs for Mg2+ ions was 8.8 mg/g scaffolds. Its adsorption isotherm fitted well with Langmuir isotherm by showing R2 of 0.9995. Fluorescence-based staining, cell viability, and alkaline phosphatase assays indicated that the adsorbed Mg2+ ions onto CTNTs scaffolds aided in promoting higher proliferation and early differentiation of MG63 cells than scaffolds without Mg2+ ions in a concentration-dependent manner. Based on current results, CTNTs scaffolds with Mg2+ ions may be a potential biomaterial for bone regeneration.